Cloropropil vermiculitas modificadas com derivados de piperazina contendo zinco e cobre como agentes antimicrobianos - Nunes Filho, Francisco Gilmário (2018)
Vermiculite is a 2:1 planar phyllosilicate, di or trioctahedric, with high isomorphic substitution and high lamellar charge, which is neutralized by hydrated ions such as magnesium. Acid activation of the vermiculite results in Si-OH sites, which react covalently with silanes. In this present work, vermiculite samples were activated in 1.00, 2.00 and 3.00 mol.L-1 HNO3 and the leached solids reacted with 3-chloropropyltrimethoxissilane. The silylated solids interacted with two cyclic amines, pyperazine (PPZ) and 1,4-Bis-(3aminopropyl)pyperazine (APPIP). Precursor and organofunctionalized solids adsorbed zinc and copper cations and were used as antimicrobial agents. The antimicrobial activity was evaluated through the minimum inhibitory concentration (MIC) tests for Staphylococcus aureus and Escherichia coli bacterias. XRD patterns of the pristine and activated solids indicated that the basal spacings were 1.42 nm before and after silylation, suggesting the immobilization of the silane on external surface of the vermiculite. New bands assigned to C-H and C-N groups were observed in the infrared spectra of the organofunctionalized solids and the mass loss associated to organic matter decomposition in the thermogravimetry curves, demonstrated the presence of organic groups in the inorganic matrix. These data were confirmed by chloride and CHN elemental analysis. The nitrogen basic centers on solids complexed copper and zinc cations from aqueous solution. The copper saturated solids presented good antimicrobial activity for both bacterias and the better MIC values were 10.4 and 20.8 mg/mL for E. coli.